Quality Assurance in Asian Distance Education: Diverse Approaches and Common Culture - Jung, Insung; Wong, Tat Meng; Li, Chen; Baigaltugs, Sanjaa; Belawati, Tian (International Review of Research in Open and Distributed Learning, 2011)
With the phenomenal expansion of distance education in Asia during the past three decades, there has been growing public demand for quality and accountability in distance education. This study investigates the national quality assurance systems for distance education at the higher education level in Asia with the aim of contributing to a better understanding of the current level of development of quality assurance in Asian distance education and to offer potential directions for policy makers when developing and elaborating quality assurance systems for distance education. The analysis of the existing quality assurance frameworks in the 11 countries/territories selected reveals that the level of quality assurance policy integration in the overall national quality assurance in higher education policy framework varies considerably. The purpose of quality assurance, policy frameworks, methods, and instruments in place are generally tailored to each country’s particular circumstances. There are, however, obvious commonalities that underpin these different quality assurance efforts.